Parasitism by cestodes in free-range chickens (Gallus gallus domesticus) - Souto, Erick Platiní Ferreira; Oliveira, Artefio Martins de; Garcia, Dlean da Silva; Dantas, Antonio Flávio Medeiros (Seven Editora, 2023)
The epidemiological, clinical and anatomopathological aspects of an outbreak of endoparasitosis in free-range chickens caused by Raillietina spp. are described.In a subsistence farm, 10 free-range chickens from a commercial farm were purchased. All birds began to manifest inappetence, hypodipsia, cachexia, reluctance to move, progressive lethargy, ventral decubitus and death. Three birds were sent for necropsy and presented cachectic body status, muscular atrophy and pale mucous membranes. In the small intestine there were numerous white cestoid helminths, segmented, with semiparallel walls, compatible with Raillietina spp. In histopathology, necrosis of the epithelial cells of the mucous tunic, lymphoplasmocytic inflammatory infiltrate permeating the mucosa and ectasia of the crypts were observed. Periodic assistance from a veterinarian is recommended, with the institution of a targeted or broad-spectrum deworming protocol. DOI:https://doi.org/10.56238/alookdevelopv1-190